Investigating Electronic Banking Services on Customer Satisfaction in Commercial Banks (Victoria Journal of Management, 2025)
This study aims to investigate of electronic banking services on customers satisfaction in commercial banks in Syangja, Nepal. With the increasing reliance on digital banking, the research is grounded in the significance of service quality, convenience, security, cost, privacy, and responsiveness in shaping customers’ experiences and overall satisfaction guided by Technology Acceptance Model (TAM) and SERVQUAL Model. A descriptive and causal comparative research design was used with a structured survey questionnaire as the instrument for data collection. The study surveyed 200 e-banking users from commercial banks, out of which 194 valid responses were obtained through random sampling. Quantitative methods, including descriptive statistics, correlation analysis, and regression analysis, were applied to evaluate the influence of key variables on customer satisfaction. The findings revealed that privacy, responsiveness, convenience, and security significantly affect customer satisfaction, while cost showed no significant impact. The results aligned with both global and local empirical studies and supported the TAM and SERVQUAL theoretical frameworks. The study concludes that Nepalese banks should focus on enhancing digital infrastructure, data privacy, and customer support to improve satisfaction. The implications are relevant for researchers, bankers, and policymakers in developing more efficient and customer-oriented e-banking services. Future research direction could be gender as moderating variables the effect of e- banking services on customer satisfaction in Nepali commercial banks.